2016
DOI: 10.1038/srep22902
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory isoforms of IL-32 as novel and robust biomarkers for control failure in HIV-infected slow progressors

Abstract: HIV-infected slow progressors (SP) represent a heterogeneous group of subjects who spontaneously control HIV infection without treatment for several years while showing moderate signs of disease progression. Under conditions that remain poorly understood, a subgroup of these subjects experience failure of spontaneous immunological and virological control. Here we determined the frequency of SP subjects who showed loss of HIV control within our Canadian Cohort of HIV+ Slow Progressors and identified the proinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 61 publications
5
55
2
Order By: Relevance
“…These observations suggest a strong link between CXCL8 through its proinflammatory action to viral replication and disease progression. On the other hand, El-Far et al (28) underlined the role of the proinflammatory IL-32 cytokine in the failure of virus replication control in HIC. We did not find any differences between HIC and cART patients in the expression of IL-32 gene in our study, where there was no failure to control viral replication, neither in HIC nor in cART patients.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest a strong link between CXCL8 through its proinflammatory action to viral replication and disease progression. On the other hand, El-Far et al (28) underlined the role of the proinflammatory IL-32 cytokine in the failure of virus replication control in HIC. We did not find any differences between HIC and cART patients in the expression of IL-32 gene in our study, where there was no failure to control viral replication, neither in HIC nor in cART patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to promoting cytokine production, overexpression of endogenous IL-32γ caused cell death, which in contrast doesn`t occur with the IL-32α isoform (15,20). The difference in the size of the isoforms, ranging from 14.9 kDa (IL-32α) to 26.7 kDa (IL-32γ), and the tertiary structure of the isoforms may be part of the explanation for their different potency (21,22). The endogenous level of IL-32 can be modulated in immune cells by exposure to various stimuli.…”
Section: Isoformsmentioning
confidence: 99%
“…Regarding the role of this cytokine in HIV-1 infections, results showed that interferons are crucial for the anti-HIV-1 effect of recombinant IL-32γ, and silencing of endogenous IL-32 reduced the levels of Th1 and proinflammatory cytokines, which confirm the anti-HIV-1 property of IL-32. Blockade of any of the interferons α, β or γ enhanced further HIV virus replication (17,(43)(44)(45). Based on link between IL-32 activity and production of IFNα, β or γ, various authors proposed that IL-32 exhibits its antiviral properties by all these interferons (39,21) (Figure 2).…”
Section: Role In Viral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific function of IL32 is still not clear, however, it has been implicated in the pathogenesis of cancer and several inflammatory diseases (12). Diseases such as rheumatoid arthritis (14), chronic obstructive pulmonary disease (15), HIV infection (16), tuberculosis (17), inflammatory bowel disease (6), rhinosinusitis (18), stomach cancer (19), renal cancer (20) and CRC (21) are closely linked to IL32.…”
mentioning
confidence: 99%